Empowering Speaking Skill through Debate: The Case of Afghan EFL Learners at Herat University - Noor, Shagofah; Tajik, Omid (Future Science / FSH-PH Publications, 2022)
Using a quantitative approach, this study investigated the impacts of debate on students’ speaking skills in English-language classes at the English Department, Herat University, Afghanistan. The study participants were 44 sophomore students (28 girls and 16 boys). To understand participants’ speaking levels, researchers had a pre-test followed by a six-week treatment of having debates in the speaking class. For measuring the impacts of debate, a speaking post-test was taken. To investigate the impacts of debate on students’ speaking skills the researchers created an online questionnaire form and the link was shared with students in speaking classes. The questionnaire enriched this study with essential information after the treatment. The data were analyzed through SPSS 25. A paired sample t-test was used to measure the degree to which students’ speaking skills developed throughout the six-week debate program, and students’ responses to the online questionnaire were analyzed by calculating the percentage of each item. The results of the present study indicate that debate had a positive impact and enhanced students’ speaking skills. The participants also reflected that debate had improved their critical thinking, helped them practice new language skills and arguments, developed collaboration, and decreased their speaking anxiety while having fun.